2006
DOI: 10.1007/s00467-006-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of 110 children and adolescents with primary focal segmental glomerulosclerosis

Abstract: The purpose of this retrospective cohort study was to report the clinical course of children and adolescents with primary focal segmental glomerulosclerosis (FSGS). The records of 110 patients with biopsy-proven FSGS admitted between 1972 and 2004 were retrospectively reviewed. Demographic, clinical and laboratory data were recorded and histopathological data were reanalyzed by one pathologist who had no information about the outcome of the patients. Renal survival analysis was performed using the Kaplan-Meier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
6
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 39 publications
3
27
6
5
Order By: Relevance
“…In a subgroup in which the mean follow-up period was almost 7 yr, the clinical features remained generally favorable during the entire observation period. These results are consistent with those of Abrantes et al (13) and Paik et al (17), who showed higher rates of renal survival in children with FSGS compared with previous studies in children and adults. The improved short-term outcome among the three recent pediatric studies is Figure 1.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In a subgroup in which the mean follow-up period was almost 7 yr, the clinical features remained generally favorable during the entire observation period. These results are consistent with those of Abrantes et al (13) and Paik et al (17), who showed higher rates of renal survival in children with FSGS compared with previous studies in children and adults. The improved short-term outcome among the three recent pediatric studies is Figure 1.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, approximately 30 to 40% of adult patients who develop FSGS will experience significant renal insufficiency within the first decade after diagnosis (7), although there is evidence that the prognosis may be less ominous in childhood primary FSGS. For example, Abrantes et al (13) showed that the probability of severe renal impairment in childhood FSGS is 8% at 5 yr, 17% at 10 yr, and 32% at 15 yr, which confirmed the data in another study of childhood FSGS (21). However, other studies in pediatric FSGS suggest a grimmer prognosis.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…5,6 Various histological variants of FSGS have been described in the past and attempts have been made to co-relate the longterm outcomes of patients with the histopathological variant. 1,[7][8][9][10] The Columbia classification of primary FSGS has defined and classified the variants into five subtypes including (1) collapsing, (2) tip lesion, (3) cellular, (4) hilar and (5) not otherwise specified (NOS). 1,7 Various studies have proved that the histological variants do have a significant impact on the long-term outcome of the patient.…”
Section: Introductionmentioning
confidence: 99%